The role of the Tambi Tea Plantation Industry in the local economy in the Wonosobo Region - Agustin, Della; Sari, Yevi Permata; Stevani, Nadia; Sipayung, Emarson; Hera, Bowo Salma; Putri, Media Utami; Monika, Eni; Siswantoro, Ariel (Central Community Development Journal, 2023)
This research aims to analyze the role of the Tambi tea plantation industry in the local economy of the Wonosobo region. A descriptive approach was used, collecting data from various primary and secondary sources such as interviews, historical documentation, and related literature. Research instruments included interview guides and observation sheets. Data analysis methods used were content analysis and descriptive statistics. Data validity was checked through data triangulation, comparing and verifying data from various sources to ensure consistency and reliability. The results showed that the Tambi tea plantation industry has played an important role in enhancing the local economy in the Wonosobo region. This research faced limitations in access due to certain areas being restricted for visitors. Limited time also constrained the depth of analysis and the number of samples that could be studied, as well as the number of respondents for interviews. The historical development of this industry also illustrates significant social and economic changes in the local community. This research provides valuable insights for local stakeholders, the plantation industry, and researchers in the fields of economics and local development.